2015
DOI: 10.1242/dev.118372
|View full text |Cite
|
Sign up to set email alerts
|

A cellular process that includes asymmetric cytokinesis remodels the dorsal tracheal branches in Drosophila larvae

Abstract: Tubular networks are central to the structure and function of many organs, such as the vertebrate lungs or the Drosophila tracheal system. Their component epithelial cells are able to proliferate and to undergo complex morphogenetic movements, while maintaining their barrier function. Little is known about the details of the mitotic process in tubular epithelia. Our study presents a comprehensive model of cellular remodeling and proliferation in the dorsal branches of third-instar Drosophila larvae. Through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Thus, shifts in polarity, which facilitate shape changes might occur during mitosis and involve specific mitotic phases. But how polarity shifts might affect events during subsequent phases of the cell cycle is not understood, although novel mechanisms that correlate junctional remodeling with cytokinesis have been recently proposed (Denes et al, 2015).…”
Section: Non-canonical Bmp-tgfβ Interactions Modulate Apicobasal Polamentioning
confidence: 99%
“…Thus, shifts in polarity, which facilitate shape changes might occur during mitosis and involve specific mitotic phases. But how polarity shifts might affect events during subsequent phases of the cell cycle is not understood, although novel mechanisms that correlate junctional remodeling with cytokinesis have been recently proposed (Denes et al, 2015).…”
Section: Non-canonical Bmp-tgfβ Interactions Modulate Apicobasal Polamentioning
confidence: 99%
“…Because of their three-dimensional structure, tubular networks have a more complex morphology than epithelial sheets. Therefore, the division of elongated and lumenized cells may require some adaptations of the mitotic machinery in order to accommodate their peculiar geometry as was recently shown in a study of the Drosophila larval trachea system ( Denes et al, 2015 ). While the actomyosin rings that drive cytokinesis in the Drosophila epithelia are able to symmetrically deform the AJs of the two cells that flank the emerging junction ( Founounou et al, 2013 ; Guillot and Lecuit, 2013 ; Herszterg et al, 2013 ), during cytokinesis in tracheal tubes, the membrane furrows asymmetrically on the side of the cell that is proximal to the nucleus, and the new junction then extends around the lumen until it connects and fuses with another membrane.…”
Section: Introductionmentioning
confidence: 95%
“…While the actomyosin rings that drive cytokinesis in the Drosophila epithelia are able to symmetrically deform the AJs of the two cells that flank the emerging junction ( Founounou et al, 2013 ; Guillot and Lecuit, 2013 ; Herszterg et al, 2013 ), during cytokinesis in tracheal tubes, the membrane furrows asymmetrically on the side of the cell that is proximal to the nucleus, and the new junction then extends around the lumen until it connects and fuses with another membrane. We found that in the remodeling dorsal tracheal branches, such asymmetric de novo junction formation is the norm, presumably because the specific geometry and the rigidity of the tubes favor this outcome ( Denes et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coordination between de novo junction formation and cell division is a general feature of monolayered tissues (Denes et al, 2015; Firmino et al, 2016; Founounou et al, 2013; Herszterg et al, 2013; Higashi et al, 2016; Jinguji and Ishikawa, 1992; Lau et al, 2015; Morais-De-Sá and Sunkel, 2013; Pinheiro et al, 2017; Reinsch and Karsenti, 1994). The coordination of TCJ formation and cytokinesis leading to the formation of a neighbour-neighbour interface has been elegantly studied in the epithelium of the gastrulating Xenopus embryo.…”
Section: Discussionmentioning
confidence: 99%